Evidence for tuberculosis in 18th/19th century slaves in Anse Sainte-Marguerite (Guadeloupe – French Western Indies). (June 2015) - Lösch, Sandra; Kim, Mi-Ra; Dutour, Olivier; Courtaud, Patrice; Maixner, Frank; Romon, Thomas; Sola, Christophe; Zink, Albert
Summary: During the American colonization in the 18th and 19th century, Africans were captured and shipped to America. Harsh living and working conditions often led to chronic diseases and high mortality rates. Slaves in the Caribbean were forced to work mainly on sugar plantations. They were buried in cemeteries like Anse Sainte-Marguerite on the isle of Grande-Terre (Guadeloupe) which was examined by archaeologists and physical anthropologists. Morphological studies on osseous remains of 148 individuals revealed 15 cases with signs for bone tuberculosis and a high frequency of periosteal reactions which indicates early stages of the disease. 11 bone samples from these cemeteries were analysed for ancient DNA. The samples were extracted with established procedures and examined for the cytoplasmic multicopy β-actin gene and Mycobacterium tuberculosis complex DNA (IS 6110) by PCR. An amplification product for M. tuberculosis with the size of 123 bp was obtained. Sequencing confirmed the result. This study shows evidence of M. tuberculosis complex DNA in a Caribbean slave population.